2018
DOI: 10.1007/s12031-018-1075-5
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells

Abstract: Mesenchymal stem cell (MSC) therapy is a promising prospect for the treatment of Alzheimer's disease (AD); however, the underlying mechanisms by which MSCs mediate positive effects are still unclear. We speculated that MSCs mediate microglial autophagy and enhance the clearance of Aβ. To test this hypothesis, we cultured BV2 microglial cells with umbilical cord mesenchymal stem cells conditioned medium (ucMSCs-CM) in the presence or absence of Aβ25-35 oligomers. We investigated BV2 cell proliferation, cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…To further explore the pathological change after hUC-MSCs transplantation, we studied neuro-inflammation in DG. A previous study demonstrated that the hUC-MSCs conditioned medium promoted the phagocytosis of Aβ25-35 by BV2 microglial cells in vitro and upregulated the expression of neprilysin and insulin-degrading enzymes, major proteases which cleave Aβ plaques (Xu et al, 2018). Aβ deposition is recognized as the main culprit for the pathological cascade of AD.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the pathological change after hUC-MSCs transplantation, we studied neuro-inflammation in DG. A previous study demonstrated that the hUC-MSCs conditioned medium promoted the phagocytosis of Aβ25-35 by BV2 microglial cells in vitro and upregulated the expression of neprilysin and insulin-degrading enzymes, major proteases which cleave Aβ plaques (Xu et al, 2018). Aβ deposition is recognized as the main culprit for the pathological cascade of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, systemic MSCcm administration further increased LC3 II/I levels in the spinal cord. The autophagy-promoting effects by MSC graft [48], MSCcm [49] or MSC exosomes [50,51] have been reported in culture or in vivo studies, although not have not been seen in an SCI rat model. Additional experiments are warranted to determine the relation and role of individual RNA, miRNA and related protein elements of exosomes and SCI autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Since an increase in the autophagy capacity of microglial cells could induce the microglia to phagocytose [43], the ability of microglia to phagocytize Aβ was tested.…”
Section: Graphene Oxide Promoted Microglia-mediated Phagocytosis Of Aβmentioning
confidence: 99%